2013
DOI: 10.1371/journal.pone.0080789
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of DLGAP5 by siRNA Significantly Inhibits the Proliferation and Invasion of Hepatocellular Carcinoma Cells

Abstract: BackgroundThe dysregulation of oncogenes and tumor suppressor genes plays an important role in many cancers, including hepatocellular carcinoma (HCC), which is one of the most common cancers in the world. In a previous microarray experiment, we found that DLGAP5 is overexpressed in HCCs. However, whether the up-regulation of DLGAP5 contributes to hepatocarcinogenesis remains unclear. Methodology/Principal FindingsIn this study, we showed that DLGAP5 was significantly up-regulated in 76.4% (168 of 220) of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 23 publications
2
54
0
Order By: Relevance
“…This protein is relatively unstudied in tumor biology, but recently was shown to have a potential role in hepatocellular cancer. Liao et al demonstrated overexpression of DLGAP5 mRNA to be common in tumor samples from liver cancer patients, and that in vitro RNA-interference mediated silencing of DLGAP5 inhibited proliferation and invasion (38). One of the novel, ATC-specific underexpressed genes was C2orf40, which encodes the esophageal cancer-related gene 4 (ECRG4) protein, a tumor suppressor affecting cancer cell migration, invasion and cell cycle regulation and downregulated in esophageal and breast cancer (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…This protein is relatively unstudied in tumor biology, but recently was shown to have a potential role in hepatocellular cancer. Liao et al demonstrated overexpression of DLGAP5 mRNA to be common in tumor samples from liver cancer patients, and that in vitro RNA-interference mediated silencing of DLGAP5 inhibited proliferation and invasion (38). One of the novel, ATC-specific underexpressed genes was C2orf40, which encodes the esophageal cancer-related gene 4 (ECRG4) protein, a tumor suppressor affecting cancer cell migration, invasion and cell cycle regulation and downregulated in esophageal and breast cancer (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…cDNA sample mixed with 20 μl Master mix (SYBR ® Green PCR Master Mix, Applied Biosystems) was amplified using the ABI Prism 7500 Sequence Detector System Applied Biosystems (Foster City, CA, USA) with the following reactive conditions: incubation at 95°C for 10 min; then 40 cycles of denaturation at 95°C for 2 sec, annealing at 55°C for 5 sec, and extension at 72°C for 15 sec. Relative DEPDC1 mRNA expression was calculated according to our previous report (Liao et al, 2013).…”
Section: 10917 Dep Domain Containing 1 Is a Novel Diagnostic Marker mentioning
confidence: 99%
“…The mean Ct value for β-actin was subtracted from the mean Ct value for RHAMM in each sample using the following formula: RHAMM ΔCt = (mean RHAMM Ct -mean β-actin Ct). The fold-change (2 -RHAMM ΔΔCt ) of the RHAMM expression level relative to the β-actin expression level was calculated for each sample (19).…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%